The synthesis of high yield Au nanoplate and optimized optical properties. (February 2018) - Ni, Yuan; Kan, Caixia; Xu, Juan; Liu, Yang
Abstract: The applications of Au nanoplates based on the tunable plasmon properties and enhanced electromagnetic field at the sharp tip and straight edges, have generated a great deal of interest in recent years, especially in the fields of the bio-chemical sensing and imaging. In this review, we focus on the synthesis of nanoscale platelike structures by multiple synthetic strategies (such as thermal solution method, seed-mediated method, seedless method, and some greener methods), and explore corresponding growth mechanism in different synthetic approaches. Other than to review the fabrication of Au nanoplates, the purification strategies are also discussed in order to support the applications in various fields. Modifying synthetic method to obtain well-defined nanoplates can tuned optical absorption from visible to near-infrared region. Moreover, the Au nanoplate dimers (vertex-to-vertex and edge-by-edge assemblies) can induce more specific plasmon properties and stronger localized field due to coupling of interparticles. Compared with 0D quasi-spherical nanoparticles and 1D nanorods, the 2D nanoplates can be applied as a good surface-enhanced Raman scattering (SERS) substrate because of the sharp corners and straight edges. This review will provide background information for the controllable synthesis of anisotropic nanoparticles and advance the application of coupled nanostructures. Highlights: Multiple synthetic strategies of Au nanoplates and purified methods. Particular optical properties of assembly nanoplates dimer. A good candidate for SERS substrate because of the enhanced EM field at the sharp corners and straight edges.